Bombus lucorum Linnaeus 1761 ... - Ornosa, Concepción; Torres, Félix; Rúa, Pilar De La (Zenodo, 2017)
Bombus lucorum (Linnaeus, 1761) Bombus lucorum occurs from southern Europe to Iceland, northern Asia to the Pacific coast. It is considered of Least Concern in the IUCN Red List of European Bees (Rasmont et al. 2006, 2015). The Pyrenean population consists of one unique subspecies: ... : Published as part of Ornosa, Concepción, Torres, Félix & Rúa, Pilar De La, 2017, Updated list of bumblebees (Hymenoptera: Apidae) from the Spanish Pyrenees with notes on their decline and conservation status, pp. 41-77 in Zootaxa 4237 (1) on page 47, DOI: 10.11646/zootaxa.4237.1.3, http://zenodo.org/record/322688 ...